Enhanced Electron Transport and Heat Transfer Boost Light Stability of Ternary Organic Photovoltaic Cells Incorporating Non‐Fullerene Small Molecule and Polymer Acceptors. (24th July 2019) - Yin, Hang; Chiu, Ka Lok; Bi, Pengqing; Li, Gang; Yan, Cenqi; Tang, Hua; Zhang, Chujun; Xiao, Yiqun; Zhang, Hengkai; Yu, Wei; Hu, Hanlin; Lu, Xinhui; et al.
Abstract: Operation stability remains the key hurdle for the best‐performing non‐fullerene small molecule acceptor (SMA)‐based organic photovoltaic (OPV) devices. Among all SMAs, the ITIC‐derivative is the most promising OPV cell using ITIC‐derivative acceptors with a power conversion efficiency > 15%. However, the operation stability of SMA‐based devices under illumination is relatively inferior when compared to bulk‐heterojunction (BHJ) cells that employ polymeric acceptors. Here, a polymer acceptor N2200 is used as the ternary component to study the device performance of ITIC‐derivative‐based PBDB‐T:ITIC‐M and PBDB‐T‐2F:IT‐4F BHJ solar cells, which currently are the representative state‐of‐the‐art high‐performance OPV devices. The ternary solar cells with low N2200 loading enjoy significantly improved operation stability, while maintaining a high power conversion efficiency. A comprehensive mechanism study is conducted on the ternary OPV systems in i) electronic and ii) thermal aspects. For i), the ternary BHJs show remarkably improved electron transport. For ii), the thermal diffusivity D of the ternary BHJ exhibits almost an order of magnitude improvement in D values, indicating that heat can be more effectively transferred out of such films than binary counterpart. The results show that N2200 ternary loading facilitates an improved network for both electron transport and heat dissipation, leading to improved photostability. Abstract : Ternary solar cells with low N2200 loading enjoy improved photostability. A comprehensive mechanism study is conducted in i) electronic and ii) thermal aspects. For i), the ternary BHJs show improved electron transport. For ii), the thermal diffusivity D of the ternary BHJ exhibits almost an order of magnitude improvement, indicating heat can be more effectively transferred out of such films.